Vladimir N. Lossky’s apophatism and its critical reception - Sutil Lorenzo, José Alberto (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
The contemporary orthodox theologian Vladimir N. Lossky (1903-1958) made apophatism or negative theology a feature of his theology, according to Eastern Christian approaches. His radicalism in this regard has been widely criticized. In this paper, we first expose the apophatism of the author studied. In this sense, we discover apophatism as a theological attitude typical of orthodox theology that is manifested in the various aspects of Christian life (the dogma of the Trinity, the dogma of divine energies, the procession of the Holy Spirit, anthropology, liturgy, icons). In a second part of the study, we go through the different contributions that make up the critical reception of Losskian apophatism (Tyszkiewicz, Florovsky, Williams, Stăniloae, Zizioulas, Rogobete, Bernardi, Prosperi, Papanikolau, Nichols, Clément), to conclude by offering our own opinion on the matter.